The Protection of Personal Data in the Context of Modern Competitive Dances in Slovenia - Turnšek, Ema (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This article examines the crossroads of dance, sports law, data protection and human rights. It outlines the data protection framework in Slovenia by analysing not only EU and national legal Acts but also specific regulations adopted by the International Dance Organisation, especially relevant for the dancers, practicing any style or category of the modern competitive dances in Slovenia or elsewhere. While these specific regulations do not provide any additional protection or added value to dancers in comparison to the general and specific laws relevant in this matter, this paper demonstrates the comprehensive and well-established nature of the legal framework that protects dancers’ personal data. Principally, the article circles around the actual state dancers’ data protection in Slovenia, which is presented through empirical research consisting of a cohort of the Slovenian dance clubs and studios registered under the Slovenian Dance Organisation.